2019
DOI: 10.3390/geosciences9010034
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Short-Term Tidal Variability of Multibeam Backscatter from Field Experiments on Different Seafloor Types

Abstract: Three experiments were conducted in the Belgian part of the North Sea to investigate short-term variation in seafloor backscatter strength (BS) obtained with multibeam echosounders (MBES). Measurements were acquired on predominantly gravelly (offshore) and sandy and muddy (nearshore) areas. Kongsberg EM3002 and EM2040 dual MBES were used to carry out repeated 300-kHz backscatter measurements over tidal cycles (~13 h). Measurements were analysed in complement to an array of ground-truth variables on sediment an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 65 publications
0
23
0
Order By: Relevance
“…Hence, by comparing the observed backscatter variations with the seafloor interface-roughness parameter (RMS roughness, slope and intercept) no significant relationships were found (Table 1). In fact, the observed lander backscatter difference (1.1 dB) may be within a natural time-varying fluctuation in sand environments [45,46] and is less than 4 dB for small patches with increased abundance of benthic life in the investigation area based on a 200 kHz ship-based multibeam echo sounder survey reported by reference [19]. The lander data-model comparison showed no correlation.…”
Section: Discussionmentioning
confidence: 71%
“…Hence, by comparing the observed backscatter variations with the seafloor interface-roughness parameter (RMS roughness, slope and intercept) no significant relationships were found (Table 1). In fact, the observed lander backscatter difference (1.1 dB) may be within a natural time-varying fluctuation in sand environments [45,46] and is less than 4 dB for small patches with increased abundance of benthic life in the investigation area based on a 200 kHz ship-based multibeam echo sounder survey reported by reference [19]. The lander data-model comparison showed no correlation.…”
Section: Discussionmentioning
confidence: 71%
“…At present, data are compiled regardless of their vintage; hence, datasets for different time periods are often combined to create a single map. In near-coastal areas with high sediment dynamics, seabed surface monitoring typically shows highly variable substrates through time, with seasonal, event-or activity-related and unexplained patterns [55]. The present phase of EMODnet has focused on the static mapping of available data, but future efforts should account for this temporal behaviour.…”
Section: Confidencementioning
confidence: 99%
“…Yet, these novel automated methods have scarcely been applied to the assessment of temporal changes in deep-water habitats [14][15][16][17], with little evidence of any attempt to conducted a systematic study to assess the suitability and repeatability of different methods in temporal change detection. To validate the use of automated methods in the monitoring of MPAs, it is necessary not only to assess their accuracy, but also to establish that they are repeatable, such that users can be confident that any differences in the resultant benthic habitat maps are the result of true changes to seafloor habitats, and not simply artefacts of the method.…”
Section: Introductionmentioning
confidence: 99%
“…This was acknowledged by Rattray et al [14], who identified the unknown repeatability of the classification process as a difficult to control source of error in the classification step when researching benthic habitat change. It has been acknowledged that current acoustic technologies provide limited repeatability depending on the instrument, equipment settings, processing algorithms, operational ranges, environmental conditions, and survey methods [17,20]. Nevertheless, there are few if any studies that have attempted to compare the repeatability of different classification algorithms.…”
Section: Introductionmentioning
confidence: 99%